METODE NEWTON RAPHSON UNTUK ANALISIS ALIRAN DAYA JARINGAN DISTRIBUSI 12,66 KV - Miftahul Fikri; Dwi Anggaini (Sutet, 2018)
Analysis the flow of power in works system electricity used to determine parameters workers system electricity. The calculation process are own related to the optimize system. A method of which has been used is the method Newton Raphson iteration. This method is a Taylor of obtaining the derivative a mathematical equation as the basis for calculation iteration involving using matric Jacobian. Analysis the flow of the power on a system electric power on useful to count some parameters that importance between another current of, voltage, power, and loss power. The method of analysis the flow of resources Newton-Raphson has been proven accurate to calculation the power on the flow of transmission system of analysis. A channel or a cable on a system the distribution of also having the ratio the resistance of versus reactance ( r / x ) that tend to high that led to the process by the calculation of the flow of power uses the method conventional above failed to converging. The results of a simulation shows that usage method of simple branch exchange to merekonfigurasi of tissues can be reduce loss of power equal to 63,4677 kw .From the results of a simulation by the use of in distribution systems ieee 33 bus 12,6 kv , shows that there has been a decrease rugi-rugi resources of a 202,6845 kw become 139,2168 kw.